Navigating the Precarious Path: Understanding the Dualisation of the Italian Labour Market through the Lens of Involuntary Part-Time Employment - Liliana Cuccu; Vicente Royuela; Sergio Scicchitano (Global Labor Organization (GLO), 2024)
This paper investigates the surge in Involuntary Part-Time (IPT) employment in Italy from 2004 to 2019, exploring its impact on various socio-economic groups and adopting a spatial perspective. Our study tests the hypothesis that technological shifts, specifically routine biased technological change (RBTC), and the expansion of household substitution services contribute to IPT growth. We uncover a widening negative gap in IPT prevalence among marginalized groups - women, young, and less skilled workers. After controlling for sector and occupation, the higher IPT propensity diminishes but remains significant, hinting at persistent discrimination. Additionally, segregation into more exposed occupations and sectors intensifies over time. Leveraging province-level indicators, and using a Partial Adjustment model, we find support for RBTC's correlation with IPT, especially among women. The impact of household substitution services is notably pronounced for women, highlighting sector segregation and gender norms' influence.
Keywords: J21; J24; O33; 330; Involuntary part-time; Precarisation of labour; Automation